Territorial threat and women's legislative representation. Issue 2 (17th February 2020) - Kang, Alice J.; Kim, Nam Kyu
ABSTRACT: Why do some countries have fewer women in parliament than do others? Recent studies find that women have less access to positions of political power in countries facing external threats. Existing studies, however, do not differentiate between types of threat. We theorize that territorial threats are a particular driver of gender inequality in national parliaments. When a country's land is under threat, people prefer having "tough" representatives in the national legislature who are competent on the military and defence more so than when a country faces other threats. Moreover, when countries face territorial threats, they build larger standing armies and adopt military conscription, raising the level of militarization in society, which negatively influences women's access to the national legislature. Using a time-series cross-sectional data set of 101 democracies, we find that countries facing external territorial threats have lower percentages of women in parliament compared to countries facing other or no external threats. Additionally, we find that countries with higher levels of militarization have fewer women in the national legislature.